2014
DOI: 10.1093/nar/gku797
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR-associated Cas4 protein Pcal_0546 from Pyrobaculum calidifontis contains a [2Fe-2S] cluster: crystal structure and nuclease activity

Abstract: Cas4 nucleases constitute a core family of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) associated proteins, but little is known about their structure and activity. Here we report the crystal structure of the Cas4 protein Pcal_0546 from Pyrobaculum calidifontis, which revealed a monomeric protein with a RecB-like fold and one [2Fe-2S] cluster coordinated by four conserved Cys residues. Pcal_0546 exhibits metal-dependent 5′ to 3′ exonuclease activity against ssDNA substrates, whereas the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 49 publications
2
48
1
Order By: Relevance
“…In addition to Cas1 and Cas2, these systems also encode Cas4 [44,45], which was recently shown to be involved in adaptation [46][47][48]. Cas4 from Bacillus halodurans type I-C system forms a complex with the Cas1 integrase and, in the presence of the Cas1-Cas2 complex, specifically cleaves the 3′ overhangs of prespacers in a PAM-dependent manner.…”
Section: Type I-cmentioning
confidence: 99%
“…In addition to Cas1 and Cas2, these systems also encode Cas4 [44,45], which was recently shown to be involved in adaptation [46][47][48]. Cas4 from Bacillus halodurans type I-C system forms a complex with the Cas1 integrase and, in the presence of the Cas1-Cas2 complex, specifically cleaves the 3′ overhangs of prespacers in a PAM-dependent manner.…”
Section: Type I-cmentioning
confidence: 99%
“…Cas4 family proteins occur widely within CRISPR-Cas adaptation modules of subtype I-A, I-B, I-C, I-D, I-U, and II-B and type V systems (2), and they include Csa1 of Sulfolobus subtype I-A systems and Csn2 of the subtype II-A systems of S. thermophilus (20) and Streptococcus pyogenes (21). High-resolution crystal structures of Cas4 proteins from S. solfataricus (33) and Pyrobaculum calidifontis (38) indicate that they carry two domains, an N-terminal RecB-like nuclease domain and a C-terminal domain containing an Fe-S cluster coordinated by four conserved cysteine residues. Moreover, biochemical studies have shown that Cas4 can exhibit 5=-to-3= and 3=-to-5= DNA exonuclease activity, as well as ATP-independent DNA unwinding activity (33,34,38), which suggests that they produce single-strand DNA overhangs that are potential intermediates for insertion of new CRISPR spacers.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution crystal structures of Cas4 proteins from S. solfataricus (33) and Pyrobaculum calidifontis (38) indicate that they carry two domains, an N-terminal RecB-like nuclease domain and a C-terminal domain containing an Fe-S cluster coordinated by four conserved cysteine residues. Moreover, biochemical studies have shown that Cas4 can exhibit 5=-to-3= and 3=-to-5= DNA exonuclease activity, as well as ATP-independent DNA unwinding activity (33,34,38), which suggests that they produce single-strand DNA overhangs that are potential intermediates for insertion of new CRISPR spacers. Previously, we have demonstrated that both Cas4 and Csa1 proteins are essential for de novo spacer acquisition (19).…”
Section: Discussionmentioning
confidence: 99%
“…Cas4 family proteins occur widely within CRISPR-Cas adaptation modules of subtype I-A, I-B, I-C, I-D, I-U, II-B, and type V systems (2) and they include Csa1 of Sulfolobus subtype I-A systems and Csn2 of the subtype II-A systems of S. thermophiles (20) and S. pyogenes (21). High resolution crystal structures of Cas4 proteins from S. solfataricus (33) and P. calidifontis (38) indicate that they carry two domains, an N-terminal RecB-like nuclease domain and a C-terminal domain containing an Fe-S cluster coordinated by four conserved cysteine residues. Moreover, biochemical studies have shown that Cas4 can exhibit 5’ to 3’ and 3’ to 5’ DNA exonuclease activity, as well as ATP independent DNA unwinding activity (33, 34, 38) which suggests that they produce single-strand DNA overhangs that are potential intermediates for insertion of new CRISPR spacers.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution crystal structures of Cas4 proteins from S. solfataricus (33) and P. calidifontis (38) indicate that they carry two domains, an N-terminal RecB-like nuclease domain and a C-terminal domain containing an Fe-S cluster coordinated by four conserved cysteine residues. Moreover, biochemical studies have shown that Cas4 can exhibit 5’ to 3’ and 3’ to 5’ DNA exonuclease activity, as well as ATP independent DNA unwinding activity (33, 34, 38) which suggests that they produce single-strand DNA overhangs that are potential intermediates for insertion of new CRISPR spacers. Previously, we have demonstrated that both Cas4 and Csa1 proteins are essential for de novo spacer acquisition (19).…”
Section: Discussionmentioning
confidence: 99%